2016
DOI: 10.2217/pgs-2016-0134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel SNPs Associated with Risk and Prognosis in Patients with Castration-Resistant Prostate Cancer

Abstract: Aim: Metabolism and transport play major roles in life-long exposure to endogenous and exogenous carcinogens. We therefore explored associations between polymorphisms in absorption, distribution, metabolism and elimination genes and the risk and prognosis of castration-resistant prostate cancer (CRPC). Materials & methods: A total of 634 genotypes were tested in 74 patients using the Affymetrix DMETv1.0 platform. Results: No relation to risk was found. Three SNPs were associated with CRPC prognosis in Caucasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This study validated that rs1045642 in ABCB1 , rs9340799 in ESR1 , and rs1395 in SLC5A6 are associated with TTP in men treated with docetaxel 22–24 . P‐glycoprotein encoded by ABCB1 is an efflux pump of taxanes involved in treatment resistance to docetaxel 22 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This study validated that rs1045642 in ABCB1 , rs9340799 in ESR1 , and rs1395 in SLC5A6 are associated with TTP in men treated with docetaxel 22–24 . P‐glycoprotein encoded by ABCB1 is an efflux pump of taxanes involved in treatment resistance to docetaxel 22 .…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, the estrogen receptor α encoded by ESR1 can affect cellular sensitivity to docetaxel through survival signaling modulated by estrogen, as supported by estrogen's effect on taxane cytotoxicity in prostate cancer cells 23,26 . However, the functional link between the sodium‐dependent vitamin transporter SLC5A6 and the anticancer effect of docetaxel is unknown 24 . In addition, this study revealed, for the first time, that rs34550074 in SLCO2A1 , rs4149117 in SLCO1B3 , and rs6051545 in GNRH2 were associated with TTP in docetaxel chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes are the only cells that convert cholesterol to bile acids ( 11 ). During the elimination of bile acids via the fecal route, new bile acids are formed from hepatic cholesterol ( 12 ). Catch-up growth occurs when LBW infants are exposed to higher levels of nutrition postnatally ( 13 ), and high-fat diets (HFDs) have been shown to contribute to postnatal catch-up growth.…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…As genetic variability in liver enzymes is often linked to interindividual variation in liver metabolism, Sissung et al hypothesised that certain variants and genes in these pathways may be behind the risk and prognosis of CRPC [29]. Patients treated with docetaxel and thalidomide and who carried variants in ABCB11 (rs7602171 GA/AA), ABCB4 (rs2302387 CT), ABCC5 (rs939339 AG), and SLC5A6 (rs1395 GA/AA) had poor OS compared to those carrying only wild-type alleles, whereas the GSTP1 rs1799811 CT genotype was associated with prolonged OS.…”
Section: Germline Genomic Biomarkers In Research Studies For Prostmentioning
confidence: 99%
“…In this small pilot study, there was suggestive evidence that SNPs in bile acid and fat catabolism genes may be related to CRPC OS. No evidence was found that any of the aforementioned SNPs were related to risk of developing CRPC [29].…”
Section: Germline Genomic Biomarkers In Research Studies For Prostmentioning
confidence: 99%